The Relationship Between Performance Evaluation, Procedural Fairness, Interpersonal Trust And Work Motivation In Private Universities - DR. Chalimah (Jurnal Ekonomi Dan Bisnis, 2015)
A university is an educational institution which also funciions as work organlzation,and contains a number or workers as its human resources. Therefore, are a university mustimplement work divisions, by building several work units. The division is implemented byclassifyng the same tipe of work in a work unit, and thereby creating several work units. Everywork units has their own tipe of work, which differs from one another, according to ihe workloadand responsibility. This classification of work will create an organizational structure containingwork units with different strata (vertical), due to their different responsibilities and workload. Itwill aLso contain several work units at the same level, because they hava same workload andresponsibility but different kind of work.All the work units must cooperate in doing their job as part of the organizational work,and in creating effective and eflicient effort in attaining their goal. The cooperation can takeplace vertically between units in different level or horizontally between unit in the same level.Universities have two main work units in its organization structure, the Academic Sectionand the Administrative Section. The academic section in responsible in conduciing teaching-learning process that is done by several lecturers, also known as academic workers. Theadministrative section is manned by several employees whose job is to support the academicsection so their work will be done in effective and efficient manner. The principal administrativesection works are mainly finance, administration, investory, and students, service. Both sectionsare important for the univesity as work and educational institution, therefore they must cooperatewith each other.The two sections are essentially different either from the type of work or from theresponsibilities they carry. They are also different in many other aspecs such as the educationalbackground requirements for the employees, the working hours, the salary and allowance,promotion requirements, and career development. As we can see that the adminisirative staff'swork are mostly routine activities which will cause boredom, doesn't need creativity and initiative,is not challenging etc. Therefore to do such, work the staff must have high motivation so theycan do their job as effective and as efficient as possible.Evidence from prior studies suggests that measures used by superiors to evaluate theirsubordinates' performance can affect the subordinates attitudes and behavior such as workmotivation (Outley, et al, 2000)However as farback as the 1970s, there is evidence to suggests the effect of performanceevaluation on subordinates' behavior may be indirect through some intervening variables. BothHopwood (1972) and Otley (2000) suggested and found that evaluative style and the type ofperformance evaluations used can affect the subordinates'perception of interpersonal trustand justness in evaluation process. Procedural fairness is important because of its likely effectson the organizational members behavior (Milani, 1975 ; Kenis, 1979; Linquist. 1995 ; Libby,1999 and Law, 2002). Inierpersonal trust is also important because successful performance evaluation is likely io occur onlg in an environment where trust among organizational memberscan develop (Hopwood, 1992). Trust is an important feature of the performance evaluationprocess because increased interpersonal trust between the subordinates and their superiors islikely to lead to improved communication (Merlinger, 1956 and Rend, 1962). In a trustingenvironment, people feel free to relate to one another and this can lead to openness amongorganization members (Reina and Reina, 1999). Trust is ihe glue of effective, humane, andefficient orqanization.